Comparison of the effects of esomeprazole 40 mg, rabeprazole 20 mg, lansoprazole 30 mg, and pantoprazole 40 mg on intragastrıc pH in extensive metabolizer patients with gastroesophageal reflux disease - Çelebi, Altay; Aydın, Dinçer; Kocaman, Orhan; Konduk, Buğra Tolga; Şentürk, Ömer; Hülagü, Sadetin (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Studies on the therapeutic efficacy of proton pump inhibitors (PPIs) in patients with gastroesophageal reflux disease (GERD) have been recently published. In most of these studies, comparison of only two PPIs have been made. There are few studies on the comparison of four or more PPIs. We aimed to compare the acid inhibitory effects of esomeprazole 40 mg, rabeprazole 20 mg, lansoprazole 30 mg, and pantoprazole 40 mg on days 1 and 5 of treatment in patients with GERD, who were extensive metabolizers in regard to the CYP2C19 genotype. Materials and Methods: Helicobacter pylori-negative with typical symptoms of GERD patients were randomly divided into four treatment groups. Efficacy analysis on days 1 and 5 were performed on the four groups which comprised 10 (esomeprazole), 11 (rabeprazole), 10 (lansoprazole), and 10 (pantoprazole) patients. Results: On day 1 of PPI treatment, the mean percentage of time with intragastric pH>4 were 54%, 58%, 60%, and 35% for the groups, respectively, and on day 5, these values were 67%, 60%, 68%, and 59%, respectively. Esomeprazole, rabeprazole, and lansoprazole were found to be superior to pantoprazole on the first day of treatment. Conclusion: Pantoprazole is a less potent proton pump inhibitor than the other PPIs tested on the first day of treatment. When the time needed to raise the intragatric pH to over 4 was evaluated, esomeprazole was found to have the most rapid action, followed by lansoprazole and rabeprazole.